A-utrophin up-regulation in mdx skeletal muscle is independent of regeneration. - Weir, A; Morgan, J; Davies, K (2004)
Duchenne muscular dystrophy is a fatal childhood disease caused by mutations that abolish the expression of dystrophin in muscle. Utrophin is a paralogue of dystrophin and can functionally replace it in skeletal muscle. A method to induce utrophin up-regulation in muscle should therefore be therapeutically useful in Duchenne muscular dystrophy. The search for such a method needs to be informed by an understanding of the mechanisms controlling utrophin expression in muscle. Two full length utrophin isoforms are expressed: A and B. A-utrophin is up-regulated in dystrophin deficient skeletal muscle and we sought to test the hypothesis that this up-regulation occurs as a consequence of ongoing regeneration. We measured utrophin expression by immunohistochemistry and immunoblotting in the oesophageal outer muscular layer and in gamma-irradiated limb muscle from mdx mice. Skeletal muscle in these tissues is dystrophin deficient but not regenerating; we found that A-utrophin up-regulation still occurred. We conclude that utrophin up-regulation in skeletal muscle does not depend on regeneration. An alternative hypothesis involving competition for binding sites between utrophin and dystrophin is discussed. These results have important implications for future studies aiming to effect therapeutic utrophin up-regulation in Duchenne muscular dystrophy patients.